A structural model for destination travel intention as a media exposure: belief-desire-intention model perspective. Issue 7 (11th July 2016) - Koo, Chulmo; Joun, Youhee; Han, Heejeong; Chung, Namho
Abstract : Purpose: Cultural exposure to a particular country through media affects people's preference for that foreign country, and may ultimately be a function of the behavior for consuming that country's cultural products – e.g., traveling to that country. Media exposure has been recognized as a major underlying reason for the desire to visit a destination. Design/methodology/approach: This study examines the impacts of potential travelers' media exposure in three different language-use groups (i.e., English, Japanese, and Chinese) and their perception of the media exposure on their intention to visit the actual site (i.e., South Korea). To enhance our understanding of the intention to visit the destination, this study proposes a research model based on use and gratification theory and the belief-desire-intention model. Findings: We found that mass and social media exposure had an effect on the intention to visit a destination as a result of the gratification and desire experienced through the content. Research limitations/implications: According to the results of an empirical analysis, our study suggests the synthesis of the use and gratification theory and the belief-desire-intention model and an examination of theoretical and practical implications. Originality/value: This study involved a sample of users of destination marketing sites. In addition, this study investigated the users' intentions to visit a real tourism destination taking into consideration mass media (traditional media) as well as social media (new media) based on the use of gratification theory and the belief-desire-intention model. Practically, the findings highlight the crucial role of social media in the intention to visit the tourism destination.